Project Management on Network and Security Development using the PMBOK Method - Iqbal, Aldy Mercyano; Setiadi, Indra Tresna; Samidi, Samidi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
HOSPITAL ABC is one of the companies that operates in the healthcare sector. In the construction of the hospitals, must be supported by the implementation of technology, especially network technology so that all operational devices in the hospital can be connected and communicate with each other, while still paying attention to the security factor on the network. Based on this, project management is needed in network and security development at the hospital to be built so that the development can be following the timeline and meet the expectations of all stakeholders. With the use of the PMBOK approach for network development and security in hospitals, every phase has very important activities and is related to other activities. Besides that, by using the PMBOK approach can also find out which parts are challenges in project implementation. In this project, the process of procuring/ordering devices, storing devices, and physically checking devices with BAST are critical parts and require more attention so that the project can run according to the specified time.